2008
DOI: 10.1124/mol.108.048447
|View full text |Cite
|
Sign up to set email alerts
|

Syntaxin 1A Interaction with the Dopamine Transporter Promotes Amphetamine-Induced Dopamine Efflux

Abstract: The soluble N-ethylmaleimide-sensitive factor attachment protein receptor protein syntaxin 1A (SYN1A) interacts with and regulates the function of transmembrane proteins, including ion channels and neurotransmitter transporters. Here, we define the first 33 amino acids of the N terminus of the dopamine (DA) transporter (DAT) as the site of direct interaction with SYN1A. Amphetamine (AMPH) increases the association of SYN1A with human DAT (hDAT) in a heterologous expression system (hDAT cells) and with native D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
183
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 119 publications
(185 citation statements)
references
References 51 publications
2
183
0
Order By: Relevance
“…Inhibition of CaMKII␣ activity using a membrane-permeable CaMKII␣ inhibitor decreased the interaction between DAT and syntaxin1A. Importantly, similar effects were obtained by inhibiting CaMKII␣ with KN-93, and it was hypothesized that AMPH-mediated activation of CaMKII␣ increases DAT-syntaxin1A interactions resulting in reversed operation of DAT (45). This is in accordance with our data showing attenuated DA release upon TAT peptides abolishing DAT C-terminal interactions, and it emphasizes the importance of CaMKII␣ for AMPH-induced DA efflux.…”
Section: H]mppmentioning
confidence: 70%
“…Inhibition of CaMKII␣ activity using a membrane-permeable CaMKII␣ inhibitor decreased the interaction between DAT and syntaxin1A. Importantly, similar effects were obtained by inhibiting CaMKII␣ with KN-93, and it was hypothesized that AMPH-mediated activation of CaMKII␣ increases DAT-syntaxin1A interactions resulting in reversed operation of DAT (45). This is in accordance with our data showing attenuated DA release upon TAT peptides abolishing DAT C-terminal interactions, and it emphasizes the importance of CaMKII␣ for AMPH-induced DA efflux.…”
Section: H]mppmentioning
confidence: 70%
“…Compelling evidence suggests that the N termini of SLC6 NTTs interact directly with syntaxin1A, possibly through an interaction with the SNARE motif H3 (Deken et al, 2000;Quick, 2003;Lee et al, 2004). For DAT, the interaction site is contained within the first 33 residues of the N terminus (Binda et al, 2008), whereas residues 30 to 54 of the GAT1 N-terminal domain were shown to interact directly with syntaxin1A (Deken et al, 2000) (Fig. 10).…”
Section: G Protein-protein Interactionsmentioning
confidence: 99%
“…AMPH is structurally similar to DA and, as a result, is transported by DAT, competing with DA during the reuptake process. AMPH also induces DAT-mediated nonvesicular release, also termed "DA efflux," a process that involves the actions of intracellular signaling proteins such as CamKIIα (12)(13)(14)(15)(16) and PKCβ (17)(18)(19), alterations in interactions with DAT-associated proteins and phospholipids (12,14,20), and changes in DAT phosphorylation (12,16,(21)(22)(23)) that biases the transporter toward an efflux-competent mechanism. Despite their mechanistic differences, MPH and AMPH both rapidly elevate DA in the CNS and are components of the most frequently prescribed medications for ADHD, Ritalin and Adderall, respectively.…”
mentioning
confidence: 99%